An Empirical Power Density‐Based Friction Law and Its Implications for Coherent Landslide Mobility. Issue 11 (2nd June 2020) - Deng, Yu; Yan, Shuaixing; Scaringi, Gianvito; Liu, Wei; He, Siming
Abstract: The evolution of the shear resistance at the base of a coherent landslide body can effectively control its dynamic behavior. High‐velocity rotary shear experiments have allowed scientists to explore stress‐strain conditions close to those found in large landslides and faults. These experiments have led to two alternative models being proposed, which describe the evolution of the shear resistance through friction laws that depend either on normal stress or on velocity. Here, we discuss an integrated approach, first proposed to study seismic fault behavior, that reconciles these two models under a single parameter—the power density—which we utilize for the first time to investigate landslide dynamics. Using thermodynamic and process‐based considerations, different soil and rock types can be related to different weakening mechanisms, which in turn can determine different landslide behaviors. Plain Language Summary: In coherent landslides, the shape and structure of the unstable soil or rock mass remains intact while it slides down. Large coherent landslides are relatively uncommon, yet they are of great concern because of their destructive power. The friction at the base of the unstable mass is a fundamental parameter that controls the movement of landslides. It can be estimated through laboratory experiments and is often assumed as a constant value. However, this assumption does not always hold, especially for large and fast‐moving landslides, where friction changes through time, or according to the velocity and thickness of the sliding mass. The dynamic stresses in large coherent landslides and seismic faults are somewhat similar. Geophysicists have proposed the concept of power density to explain the behavior of faults. Here, for the first time, we apply this concept to landslides. We analyze data from 280 published experiments on soils and rocks, showing how the power density correlates with friction for various minerals. By discussing the mechanical and thermodynamic processes that are involved, we provide a framework to link the behavior of coherent landslides to physicochemical parameters using the power density concept. Key Points: A power density‐dependent friction law can be used to describe the runout of coherent landslides Different minerals are associated with different frictional weakening mechanisms, likely determining different landslide dynamics The rate of frictional weakening seems sample size dependent: Much faster weakening may occur in landslides than in the laboratory